Determinants of excessive screen time among children under five years old in Selangor, Malaysia: a cross-sectional study - Raj, Diana; Mohd Zulkefli, Norafiah; Mohd Shariff, Zalilah; Ahmad, Norliza (MDPI, 2022)
Excessive screen time interferes with the health and development of children. However, the screen time situation among Malaysian children remains poorly understood. This study aims to identify the prevalence and determinants of excessive screen time among children under five years in Selangor, Malaysia, using the latest World Health Organization guidelines. In this cross-sectional study, 489 parent–child dyads were randomly selected from nine government health clinics in Petaling district, Selangor. Total screen time and factors were assessed using validated self-administered questionnaires and analysed using multiple logistic regression. The overall prevalence of excessive screen time was 91.4% with a median of 3.00 h. The majority of children utilized television (66%), followed by handheld devices (30%) and computers (4%). Determinants of screen time identified were Malay ethnicity, (aOR 3.56, 95% CI 1.65–7.68), parental age of ≥30 years (aOR 3.12, 95% CI 1.58–6.16), parental screen time >2 h a day (aOR 2.42, 95% CI 1.24–4.73), moderate self-efficacy to influence a child’s physical activity (aOR 2.29, 95% CI 1.01–5.20) and the positive perception on the influence of screen time on a child’s cognitive wellbeing (aOR 1.15, 95% CI 1.01–1.32). Parents play an important role in determining their child’s screen time. Future interventions should focus on addressing parental determinants to ensure age-appropriate screen time.